Class 1 integronase gene and tetracycline resistance genes tetA and tetC in different water environments of Jiangsu Province, China - Zhang, Xuxiang (Ecotoxicology (London, England), 2009)
Class 1 integronase gene (intI1) and tetracycline resistance genes (tetA and tetC) from various environmental sites in Jiangsu Province (China) were detected using qualitative PCR (polymerase chain reaction) and quantified with SYBR Green-based qRT-PCR (quantitative real-time PCR) in this study. Qualitative PCR assays demonstrated that intI1, tetA and tetC occurred in the water environments of Taihu Lake, the Nanjing section of the Yangtze River, a sewage treatment plant (STP) in Nanjing City, and two drinking water treating bioreactors. qRT-PCR results showed that abundance of intI1 in lake water and sediments was lower than the tet genes, for a given sample site and date (P < 0.05). On a volumetric basis, lake sediments contained higher concentrations of the three genes by four to five orders of magnitude than water samples, and lake water and sediments sampled in April contained fewer copies of all the genes than the samples collected in June and August (P < 0.05). The levels of intI1, tetA and tetC in the Yangtze River water increased significantly after the river flowed through Nanjing City (P < 0.05). 94.1% integron, 97.2% tetA and 98.3% tetC were removed by the activated sludge process in the STP, and more than 80% of each gene was removed in both of the two biofilters in terms of relative concentration based on sample volume. However, on the basis of DNA mass, lower removals were obtained for both the activated sludge and biofiltration processes